Sensitivity of grapevine powdery mildew (Erysiphe necator) to demethylation inhibitor and quinone outside inhibitor fungicides in New Zealand - Beresford, R.M.; Wright, P.J.; Wood, P.N.; Agnew, R.H. (New Zealand Plant Protection, 2016)
Isolates of Erysiphe necator from Hawkes Bay and Marlborough vineyards were tested for sensitivity to three demethylation inhibitor (DMI) fungicides (myclobutanil penconazole and cyproconazole) and one quinone outside inhibitor (QoI) fungicide (trifloxystrobin) Mean colony diameter was determined in a detached grape leaf assay for approximately 20 isolates per vineyard at 1 and 10 mg/litre of each fungicide Resistance to trifloxystrobin was prevalent in Hawkes Bay and Marlborough Mycobutanil resistance was found in both regions but particularly in Marlborough There was some loss of sensitivity to penconazole particularly in Marlborough Cyproconazole showed greater efficacy against E necator than the other two DMIs tested There was no explanation for the high trifloxystrobin resistance in sampled vineyards with few reports of trifloxystrobin use For DMIs there was a strong relationship between number of DMI fungicide applications over 10 years and DMI resistance across all three DMI active ingredients in both regions